Digital culture in virtual university / Mohd Sazili Shahibi - Shahibi, Mohd Sazili (UiTM Press, 2023)
Digital culture is an important element in an educational institution for several reasons, the most important of which is that it facilitates digital transformation. What is digital culture, and why is it important? What are the current challenges of the digital culture within virtual education? How does the digital tool support virtual higher education? Who are the key players that support the changes in culture during the transition of traditional pedagogy into modern pedagogy? This book discusses further the digital culture, the current scenario, the usage of digital technology and how to embrace the digital culture, types of digital tools, and the hegemony of digital culture. Several obstacles prevent digital culture from being fully embraced for better digital transformation. Personal challenges, socio-environmental challenges, forces challenges, digital leadership challenges and technical challenges are all factors that prevent the academic community from adopting a digital transformation culture. These challenges will now have a direct impact on the education sector. Primarily, it will slow down the implementation of online learning in higher education institutions. The sustainability and well-being of learners are also discussed in light of these challenges, which is an area that the lack of digital transformation adoption will impact. More importantly, long-term well-being is an important factor in producing world-class graduates on a global scale.